2009
DOI: 10.2165/11319530-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Status as an Indicator of Mortality in an Elderly Population

Abstract: This study points to the importance of excessive polypharmacy as an indicator for mortality in elderly persons. This association needs to be confirmed following adjustment for co-morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
196
5
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(221 citation statements)
references
References 36 publications
9
196
5
11
Order By: Relevance
“…27 This is perhaps related to the different definitions of polypharmacy used; we chose to analyze it as a continuous variable defined by the total number of drugs taken. Recently, Richardson et al 28 have reported a variation over time in this association; a strong independent association between polypharmacy and mortality can be found in the short term (first 2 years) for both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…27 This is perhaps related to the different definitions of polypharmacy used; we chose to analyze it as a continuous variable defined by the total number of drugs taken. Recently, Richardson et al 28 have reported a variation over time in this association; a strong independent association between polypharmacy and mortality can be found in the short term (first 2 years) for both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by the addition of new medications by the patient's various medical physicians as an outpatient. As the number of medications increases, so does the risk of having a drugdrug interaction [46]. Often additional medications are prescribed to manage the side effects of the existing medications and the list lengthens.…”
Section: Preoperative Assessment and Preparation For Surgerymentioning
confidence: 99%
“…Although polypharmacy has no generally accepted definition, most often it is defined by cut-offs, in terms of the number of medications taken, ranging from two to ten (9)(10)(11)(12). However, regardless of the definition, its prevalence has been reported to rise with age, and is associated with an increased risk of inappropriate drug prescription, under-use of effective treatment, medication errors, poor adherence to pharmacological therapies, drug/drug and drug/disease interactions, and adverse effects (3,(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%